(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The article on "Teaching Methodology of Electronics and Circuits Subject Based on Digital Technologies" aims to enhance the teaching process in the field of electronics and circuits. These methodologies facilitate identifying teaching objectives, organizing teaching materials, utilizing interactive teaching methods, practical exercises, group work, individual guidance, and involvement in scientific activities in real life. This series of activities supports theoretical and practical knowledge enhancement and their integration with the field.